On theoretical engorgement and the myth of fair value accounting in China: a reply. Issue 1 (10th September 2021) - Bewley, Kathryn; Graham, Cameron; Peng, Songlan
Abstract : Purpose: This article is a reply to "On theoretical engorgement and the myth of fair value accounting in China" Nobes (2019) from the authors of "Adaptability to fair value accounting in an emerging economy: A case study of China's IRFS convergence" (Peng and Bewley, 2010) and "The Winding Road to Fair Value Accounting in China: A Social Movement Analysis" (Bewley et al., 2018). Design/methodology/approach: This article engages directly with the arguments of the criticism. Findings: This article argues that the author of the commentary misunderstands the purpose, content and findings of both papers. By providing only a narrowly focused technical analysis of the new Chinese accounting standards, the author fails to see that their qualitative research approach reveals important, complex social and political factors at play in China's attempts to adopt modern international accounting principles. The commentary expresses a view that accounting is a neutral technology that needs only to be clearly defined and enumerated to be correctly implemented, whereas this research takes a much broader and deeper perspective. The authors seek to understand how China was able to successfully adopt fair value accounting standards in 2006, whereas an earlier attempt to introduce fair value in 1998 had led to abuse of fair value measurements and the eventual repeal of fair value regulations in 2001. Practical implications: This article helps clarify the purpose of qualitative accounting research, the role of theory in such research and the usefulness of theory in describing and explaining empirical case facts related to changes in accounting standards, particularly in an international context. Originality/value: This article contributes to a better appreciation of qualitative accounting research.